Non-isothermal melt crystallization kinetics of poly(3-hydroxybutyrate), poly(butylene adipate-co-terephthalate) and its mixture - Ito, Edson Noriyuki (2021)
Nonisothermal crystallization and melting of the biodegradable thermoplastics poly(3-hydroxybutyrate) (PHB), poly(butylene adipate-co-terephthalate) (PBAT), and a 1:1 PHB/PBAT blend were investigated by differential scanning calorimetry (DSC) over an extensive range of heating/cooling rates (2 to 64°C/min). The different phase transition behavior of the neat components was reflected in the mixture and suggest an immiscible blend. Pseudo-Avrami, Ozawa and Mo classical macrokinetic models were used to describe the evolution of the melt crystallization process. Results suggest that none of these models could be used to predict the experimental results of crystallization kinetics of the blend with sufficient precision for polymer processing applications. However, some methods may be of used for the neat resins over restricted ranges of cooling rate, temperature or conversion (e.g., Ozawa for PHB at low cooling rate, Mo for PBAT)